Where exactly did A. S. Eddington observe the solar eclipse of 29 of May 1919? - Latas, Joana (2020)
The team led by astronomer A.S. Eddington observed the total solar eclipse of 29 May 1919 from Sundy Plantation situated on the African island of Príncipe. Together with observations made in Brazil by the other British team, these results proved the light-ending prediction put forward by Albert Einstein. Over the past 100 years, during a long period of inattention, plaques were erected at Sundy Plantation at different times and at various locations to commemorate this important scientific event. With one exception, the locations of these plaques varied, mainly as a result of logistical constraints, rather than historical research. At the centenary celebrations of the 1919 eclipse organized by Eddington at Sundy: 100 Years Later, the exact site where the observations took place was identified. As a result of interdisciplinary teamwork involving experts in history of science, mathematics, architecture and anthropology, members of the local community and a Santomean artist, the exact location of the observations has now been artistically sign-posted. This research paper discusses the convoluted process that led to this identification. Furthermore, it argues that besides the intrinsic value of interdisciplinary research, this identification empowered local communities by enhancing their collective memory of a ground-breaking scientific event that is indelibly tied to their past, while boosting their development through scientific education and communication.